Vulnerability assessment of smallholder maize farmers to climate change risks and willingness to adopt climate-smart agriculture in Limpopo Province South Africa - Machete, Koketso Cathrine (My University, 2024)
Maize holds an essential position of the primary grain crop in South Africa, being a significant source of feed for animals and staple food among rural communities. Due incompetent farming techniques that smallholder farmers frequently employ, maize is more susceptible to the effects of climate change, especially intense heat waves and irregular rainfall. South African smallholder farmers’ need adjustment towards learning new farming techniques as they mitigate and adapt to changing climate. Hence, it becomes imperative to understand farmers’ willingness to adopt Climate-smart agriculture (CSA) and factors influencing willingness to adopt CSA. This study aimed to examine the vulnerability of maize farmers to climate change risks and analyze their willingness to adopt (WTA) CSA by profiling their socioeconomic characteristics, assessing their vulnerability to climate change risks, and analysing socioeconomic factors influencing their WTA CSA. About 219 smallholder farmers were purposively selected using Purposive Snowball sampling method. Cross-sectional primary data was used where information was gathered using structured questionnaires by conducting face to face and Focused Group Discussions (FGDs). The study was conducted at Ga-Makanye, Gabaza and Giyani (Dzingidzingi village) located in Limpopo Province of South Africa. Measure of dispersion, Vulnerability Index Assessment, Double-hurdle model, and WTA through CVM were utilised to the research objectives. The study used mixed method to analyse the quantitative and qualitative data. Results indicate that 81%, 67% and 63% of respondents were willing to adopt CSA in Ga-Makanye, Gabaza and Giyani, respectively. Gabaza and Giyani had more female farmers as compared to males with 77% and 70, 8%, respectively and Ga-Makanye had an equal gender distribution of sampled farmers. The results infer that a total of 75% were vulnerable to climate change risks such as relatively high temperatures with limited rainfall for a longer (drought). The econometric results were addressed using the Double-Hurdle Model and were statistically significant at 5%. Smallholder maize farmers’ education, crop diversification, and information about CSA positively influenced the WTA CSA while agricultural experience and household size negatively influenced the WTA CSA. The study recommends that the Department of Agriculture, Land Reform and Rural Development together with various agricultural stakeholders should enhance knowledge from extension officers within the area through provision of climate-smart agriculture workshops and education and encourage scientist to innovate new crops that suit CSA and farmers to diversity into new drought tolerant crops amongst other interventions.
Thesis (M. Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2024
Keywords: Vulnerability; Climate change; Climate Smart Agriculture; Ga-Makanye; Gabaza and Giyani (Dzingidzingi village); Farmers -- South Africa -- Limpopo; Corn -- Drought tolerance; Climatic changes -- South Africa -- Limpopo; Farms, Small -- South Africa -- Limpopo